Desempenho térmico de habitações unifamiliares de interesse social com paredes de concreto armado na zona bioclimática 2 brasileira - Carvalho, Paula Pereira (2012)
This research aims to evaluate the thermal performance of housing built with the technology of reinforced concrete walls executed on site, for use in Brazilian Bioclimatic Zone 2. The study was conducted through in situ measurements of air temperature inside the four main types of single family housing of social interest of Zilda Arns allotment, in the town of Santa Maria-RS. Measurements were made in winter and summer, with the housing closed and also with the housing closed with sealing in places susceptible to air infiltration. The evaluations were made from the relationship between changes in internal temperatures and outdoor temperatures, and considering the influences of solar orientation and air infiltration, and internal thermal comfort through a comparative analysis of temperatures with ASHRAE (2004) limits. It was observed that the solar orientation has influence during winter and summer, however the air infiltration has little influence on thermal performance of housings. It was also observed that the building system provides good thermal performance for the summer period, but is not suitable to Bioclimatic Zone 2 during winter. As for thermal comfort, the housings presented cold discomfort for the whole period of winter and presented comfort in most of the analyzed summer period.